Remote Work and Emotion Management in Times of COVID-19: A Perspective of Master’s Degree Students as Workers, Lima-Peru (2020) - Uribe Kajat, Justina (2021)
The main objective of this study is to determine the relationship between remote work and emotion management. It also aims to determine the relationship between the dimensions “working hours”, “work and technological support” and “social wellness”, and the emotion management variable. A methodology based on a quantitative approach with a descriptive-correlational and cross-sectional scope was used on a sample of 148 master’s degree students of the School of Administration of Universidad Nacional Mayor de San Marcos. Likert-type scale surveys were used to gather data. The methods of analysis used were descriptive and correlational. The results indicate that the variables remote work and emotion management are positively and moderately correlated (0.465); therefore, it is concluded that remote work and all its dimensions are related to emotion management.